Gut site and sex-specific enrichment of bacterial taxa and predicted metabolic pathways in wild American black bear (Ursus americanus) - Erin A. McKenney; Erik De Jesus; Taylor Hatfield; Dorian Hayes; Kaleb Holder; Christian Ivarsson; Natalie Morais; Hunter Payne; Kalle Simpson; Adrianna M. Staal; Holly Thompson; Rachael Hildreth; et al. (PLoS ONE, 2026)
American black bears’ ( Ursus americanus ) omnivorous feeding strategy, simple gut morphology, and rapid transit time prevent regulation of the gut microbiome (GMB). We analyzed stable isotopes and 16S rRNA sequences from 48 wild bears to assess the impacts of diet, age, gut site, and sex on GMB composition and PICRUSt2-predicted functional pathways. While alpha and beta diversity did not differ, we identified bacterial taxa and predicted pathways enriched based on gut site and sex. Enterococcus, Incertae, Papillibacter , and Shuttleworthia were enriched in jejunum samples (linear discriminant analysis effect size ≥ 3.5, p = 0.0374); and 6 genera drove colonic Bray-Curtis distances (SIMPER): Weisella (p = 0.0099), Anaeroplasma (p = 0.0495), Megamonas (p = 0.0099), Cellulosilyticum (p = 0.0495), Escherichia-Shigella (p = 0.0396) and Ochrobactrum (p = 0.0297). EdgeR identified isoflavonoid biosynthesis (p-adj = 0.001) and isoterpenoid biosynthesis (p-adj = 0.006) enriched in the colon, and SNARE interaction in vesicular transport (p-adj = 0.000) and secondary bile acid synthesis (p-adj = 0.005) enriched in females. Our findings provide nuanced insights to specific taxa and putative metabolic pathways that reflect sex and gut site differences in black bears, with important implications for understanding bear physiology and informing wildlife management.